Pengaruh Role Conflict dan Social Support terhadap Kepuasan Mahasiswa pada Perguruan Tinggi Swasta - Dinda Putri Novianti; Azizah Indriyani; Indah Dewi Mulyani; Andi Yulianto; Gian Fitralisma (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the influence of role conflict and social support on the learning satisfaction of employee class students in higher education. Employee-class students face complex challenges in balancing roles as workers and students, which has the potential to create role conflicts and negatively impact academic satisfaction. Instead, social support from the surrounding environment—including family, co-workers, and educational institutions—can serve as a protective factor that increases learning satisfaction. This study uses a quantitative approach with a correlational descriptive method. The research population consisted of 258 employees in Tegal City, all of which were sampled through total sampling techniques. The research instrument was in the form of a standardized questionnaire, and the data were analyzed using multiple linear regression with the help of SPSS software. The results of the study show that role conflict has a negative and significant effect on student satisfaction, while social support has a positive and significant effect. Simultaneously, these two variables make a significant contribution to student learning satisfaction. These findings confirm the importance of role conflict management strategies and strengthening social support in creating a more optimal learning experience for employee class students. The practical implications of this research can be a reference for educational institutions in designing policies and services that are responsive to the needs of working students.